Quinone Methide‐Based Organophosphate Hydrolases Inhibitors: Trans Proximity Labelers versus Cis Labeling Activity‐Based Probes. (26th November 2020) - Dubovetskyi, Artem; Cherukuri, Kesava Phaneendra; Ashani, Yacov; Meshcheriakova, Anna; Reuveny, Eitan; Ben‐Nissan, Gili; Sharon, Michal; Fumagalli, Laura; Tawfik, Dan S.
Abstract: Quinone methide (QM) chemistry is widely applied including in enzyme inhibitors. Typically, enzyme‐mediated bond breaking releases a phenol product that rearranges into an electrophilic QM that in turn covalently modifies protein side chains. However, the factors that govern the reactivity of QM‐based inhibitors and their mode of inhibition have not been systematically explored. Foremost, enzyme inactivation might occur in cis, whereby a QM molecule inactivates the very same enzyme molecule that released it, or by trans if the released QMs diffuse away and inactivate other enzyme molecules. We examined QM‐based inhibitors for enzymes exhibiting phosphoester hydrolase activity. We tested different phenolic substituents and benzylic leaving groups, thereby modulating the rates of enzymatic hydrolysis, phenolate‐to‐QM rearrangement, and the electrophilicity of the resulting QM. By developing assays that distinguish between cis and trans inhibition, we have identified certain combinations of leaving groups and phenyl substituents that lead to inhibition in the cis mode, while other combinations gave trans inhibition. Our results suggest that cis ‐acting QM‐based substrates could be used as activity‐based probes to identify various phospho‐ and phosphono‐ester hydrolases, and potentially other hydrolases. Abstract : Internal affairs : Phosphoester substrates that release electrophilic quinone‐methides were applied as activity‐based probes in three phosphotriesterases that differ in mechanism and level of activity. Their substrates′ reactivity, and mode of labeling, were systematically investigated with the aim of achieving specific cis labeling rather than trans .